Modelo de aseguramiento de la calidad para el servicio de clínica de especialidades del Hospital Pediátrico Baca Ortíz - Pérez Ávila, Verónica Alexandra (2011)
A set of planned and systematic actions arises, implemented within the quality system as far as health is concerned. These actions must be demonstrable to provide adequate confidence (both at the same Hospital and customers) that the requirements of the Quality System are met; and is therefore to be launched as a pilot in the Clinical Pediatric Specialty Hospital "Baca Ortiz".